Japan in the World, the World in Japan Fifty Years of Japanese Studies at Michigan - Center for Japanese Studies - The University of Michigan (University of Michigan Press, 2020)
In fall 1997 the Center for Japanese Studies at The University of Michigan celebrated its fiftieth anniversary. The November symposium featured more than fifty speakers, moderators, and musicians who celebrated the occasion and offered reminiscences on the Center's multifaceted scholarly and professional missions, discussions of the accomplishments of its al-umni/ae, and perspectives on wartime and postwar Japan-U.S. relations. As the first American interdisciplinary institute devoted to education and research on Japan, The University of Michigan Center for Japanese Studies has a path-making legacy. This volume, which includes the public presentations from the November 1997 symposium, reflects that legacy and the university's long and continuing involvement in Asia, which dates back to the 1870s.